(untitled) (Journal of Pathology of Nepal, 2018)
Background: Although nuclear criteria are considered to be characteristic for papillary thyroid carcinoma, some cases do raise controversy as being papillary thyroid carcinoma or non-papillary thyroid carcinoma due to unclear diagnostic nuclear features. Immunohistochemical markers can help in identifying PTC. Trophoblastic cell surface antigen 2 (TROP-2) is a novel marker that is recently applied on thyroid. The aim of this study was to evaluate TROP-2 expression and diagnostic utility in PTC compared to other thyroid nodules with follicular pattern on tissue specimens and cell block sections. Materials and Methods: This retrospective study was carried out at National Cancer Institute, Cairo University between January 2010 and January 2015. Immunohistochemical evaluation of TROP-2 was applied on archival 110 surgically excised and 66 cytological cell blocks of PTC and other follicular thyroid nodules. Membranous staining, with or without cytoplasm, was considered positive. Results: Among excised specimens, 85.1% of PTC demonstrated TROP-2 staining. The majority revealed diffuse staining. No significant staining difference was reported between studied classic and non classic variants. TROP-2 sensitivity and were 85.1% and 94.4%. Among cytological materials, all PTC were positive except two (false negative) and only two follicular adenomas were positive (false positive). TROP-2 sensitivity and specificity were 93.8% and 94.1%. None of nodular hyperplasia or adjacent normal thyroid tissues showed TROP-2 immunoreactivity either on histopathological or cytological sections. Conclusion: TROP-2 positivity was significantly higher in PTC compared to all other studied non PTC lesion in both surgical pathology specimens and cytological materials. No reported significant staining difference among studied PTC variant.